Solutions to Accelerate the Availability of new AI Robust Tools for Digital Radiography - Sylvain Genot (e-Journal of Nondestructive Testing, 2026)
By taking advantages of the strong capacities in Research and Development of FUJIFILM Medical and thanks to recent innovations in image processing and new tools based on Artificial Intelligence, FUJIFILM NDT is now able to significantly accelerate the training of new models. Radiographic images annotated by inspectors allows to supply Deep Learning models but requires a huge amount of data and a very long period to produce and then to collect all of them. To face urgency of needs from the field, FUJIFILM NDT defined a new process to accelerate the availability of new AI robust tools for digital radiography from a limited amount of data : the combination of image processing and specific approaches reduce significantly their time-to-market. Time gains during digital radiographic images inspections phase tests and robustness of insights detection are just amazing for all kinds of digital radiography. Regarding the Non-Destructive Evaluations 4.0, these new tools may represent the key factors of an advanced automation of these processes.